Corticospinal excitability is influenced by the recent history of electrical digital stimulation: implications for the relative magnitude of short-latency afferent inhibition - Bonnesen, Marie Trolle; Soren Asp Fuglsang; Hartwig Roman Siebner; Christiansen, Lasse (bioRxiv, 2022)
Background Electrical stimulation of the hand can suppress the motor evoked potential (MEP) elicited by transcranial magnetic stimulation (TMS) of the primary motor hand area (M1-HAND) when the afferent stimulus arrives in M1-HAND at the time of TMS. The magnitude of short-latency afferent inhibition (SAI) is expressed as the ratio between the conditioned and unconditioned MEP and is widely used to probe sensorimotor interactions in human physiological studies. Objective/Hypothesis We hypothesized that corticospinal excitability and SAI are influenced by the recent history of peripheral electrical stimulation. Methods In twenty healthy participants, we recorded MEPs from the right first dorsal interosseus muscle. MEPs were evoked by single-pulse TMS of the left M1-HAND alone (unconditioned TMS) or by TMS preceded by electrical stimulation of the right index finger ('homotopic' conditioning) or little finger ('heterotopic' conditioning). The three conditions were pseudo-randomly intermixed or delivered in blocks in which a single condition was repeated five or ten times. MEP amplitudes and SAI magnitudes were compared using linear mixed effect models. Results All stimulation protocols consistently produced SAI, which was stronger after homotopic stimulation. Randomly intermingling the three stimulation conditions reduced the relative magnitude of homotopic and heterotopic SAI as opposed to blocked stimulation. The apparent attenuation of SAI was caused by a suppression of the unconditioned but not the conditioned MEP amplitude during the randomly intermixed condition. Conclusion(s) The recent history of afferent stimulation modulates corticospinal excitability. This 'history effect' impacts on the relative magnitude of SAI depending on how conditioned and unconditioned responses are intermixed and needs to be taken into consideration when probing afferent inhibition and corticospinal excitability. Competing Interest Statement Hartwig R. Siebner has received honoraria as speaker from Sanofi Genzyme, Denmark and Novartis, Denmark, as consultant from Sanofi Genzyme, Denmark and as senior editor (NeuroImage) from Elsevier Publishers, Amsterdam, Netherlands. He has received royalties as book editor from Springer Publishers, Stuttgart, Germany.